2013
DOI: 10.1021/ie302643g
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of the Presence of Solid Diluents during Zn Oxidation by CO2

Abstract: We consider the solar thermochemical production of H2 and CO (syngas) from H2O and CO2 via a two-step ZnO/Zn redox cycle. The first step, driven by concentrated solar radiation, is the endothermic thermolysis of ZnO producing a gaseous mixture of O2 and Zn-vapor, which upon quenching precipitates a solid residue comprising Zn and ZnO in variable ratios. The second, nonsolar step is the exothermic oxidation of Zn by H2O and/or CO2 to form fuel (H2 and/or CO) and the solid product ZnO which is recycled to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Recent research has demonstrated that the ZnO contamination of Zn produced by solar thermal reduction of ZnO in fact facilitates the oxidation of the metallic Zn with either CO 2 or H 2 O. 21 , 22 It has been shown that the oxidation of solar Zn by CO 2 could be almost completed at temperatures as low as 350 °C in the matter of minutes (∼90% conversion in 180 s). 22 This reaction time is indeed 2-orders of magnitude longer than the residence time reported for the equivalent conversion of Zn vapor (∼1 s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has demonstrated that the ZnO contamination of Zn produced by solar thermal reduction of ZnO in fact facilitates the oxidation of the metallic Zn with either CO 2 or H 2 O. 21 , 22 It has been shown that the oxidation of solar Zn by CO 2 could be almost completed at temperatures as low as 350 °C in the matter of minutes (∼90% conversion in 180 s). 22 This reaction time is indeed 2-orders of magnitude longer than the residence time reported for the equivalent conversion of Zn vapor (∼1 s).…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 It has been shown that the oxidation of solar Zn by CO 2 could be almost completed at temperatures as low as 350 °C in the matter of minutes (∼90% conversion in 180 s). 22 This reaction time is indeed 2-orders of magnitude longer than the residence time reported for the equivalent conversion of Zn vapor (∼1 s). 20 However, becaue of the difference between the feedstock densities (∼0.7 kg/m 3 for Zn-vapor at 1000 °C versus ∼440 kg/m 3 for solar Zn containing only 25 wt % Zn 23 ) the reactor volumes required for oxidizing solar Zn and Zn-vapor at the equivalent fuel productivity are about the same.…”
Section: Introductionmentioning
confidence: 99%
“…This step need not be solaraided and since the two steps are decoupled, the production of H 2 and/or CO can be carried out on demand and round-the-clock at convenient sites and independent of solar energy availability [66]. Non-solar exothermic oxidation of Zn by H 2 O and/or CO 2 to form fuel (H 2 and/or CO) has been investigated [67]. It was shown that the presence of inert ZnO affects both the oxidation kinetics and the final asymptotic conversion of Zn.…”
Section: The Zno/zn Cyclementioning
confidence: 99%
“…Such cast objects made of 1:3 Co 0. 67 were tested for cyclic TR/WS in a typical, laboratory-scale, non-solar-heated flow reactor between approximately 1673 K (TR) and 1273 K (WS). Structural integrity could be maintained over successive cycles, however only the first composition was proved capable of cyclic WS/TR operation.…”
mentioning
confidence: 99%
“…Nonsolar exothermic oxidation of Zn by H 2 O and/or CO 2 to form fuel (H 2 and/or CO) has been investigated (Stamatiou, Steinfeld, & Jovanovic, 2013). The presence of inert ZnO affects both the oxidation kinetics and the final asymptotic conversion of Zn.…”
Section: The Zn/zno Cyclementioning
confidence: 99%